Calcium-based low-temperature desulfurizer based on channel regulation technology and preparation method and application thereof

CN120094389BActive Publication Date: 2026-10-30SHAANXI UNIV OF SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510276404.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2026-10-30
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种基于孔道调配技术的钙基低温脱硫剂及其制备方法和应用,用以解决传统的干法钙基脱硫剂脱硫效率低下的技术问题

Benefits of technology

本发明公开了一种基于孔道调配技术的钙基低温脱硫剂的制备方法,通过在体系中添加粘结剂、活性剂、造孔剂和溶解剂作为原料,由于偶氮二甲酸二乙酯和尿素具有较强的造介孔性能,掺入沸石增加脱硫剂的微孔数量,添加偶氮二甲酸二乙酯或尿素使脱硫剂生成介孔,改善了脱硫剂内部传质性能。能够构建立体的孔道结构,立体的孔道结构,解决传统的干法钙基脱硫剂脱硫效率低下的技术问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005304371500000011
    Figure HDA0005304371500000011
  • Figure HDA0005304371500000012
    Figure HDA0005304371500000012
  • Figure HDA0005304371500000021
    Figure HDA0005304371500000021
Patent Text Reader

Abstract

The application discloses a calcium-based low-temperature desulfurizer based on a pore regulation technology and a preparation method and application thereof, and belongs to the technical field of desulfurizer preparation. A binder, a pore-forming agent and an active agent are added into the system as an active additive, a mixture of zeolite and one of diethyl azodicarboxylate, diisopropyl azodicarboxylate, urea and ammonium carbonate is used as the pore-forming agent, and the remaining materials are combined. Since diethyl azodicarboxylate and the like have strong mesopore-forming properties, the number of micropores of the desulfurizer is increased by adding zeolite, diethyl azodicarboxylate or other substances are added to make the desulfurizer generate mesopores, and the internal mass transfer performance of the desulfurizer is improved. The desulfurizer can be constructed to have a three-dimensional pore structure, the micropore area of the desulfurizer is improved, the mass transfer channel is improved, and the desulfurization performance is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of desulfurizing agent preparation technology, specifically relating to calcium-based low-temperature desulfurizing agents based on pore channel adjustment technology, their preparation methods, and applications. Background Technology

[0002] Flue gas desulfurization (FGD) is one of the current desulfurization methods. Its principle mainly involves various alkaline absorbents or adsorbents reacting physically or chemically with SO2 in the flue gas, converting it into relatively stable and easily mechanically separable sulfates or sulfites. Since the 1960s, countries worldwide have vigorously developed and applied flue gas desulfurization technology. Flue gas desulfurization is further divided into dry desulfurization, semi-dry desulfurization, and wet desulfurization technologies.

[0003] Dry flue gas desulfurization (FGD) technology refers to the removal of SO2 from flue gas by using desulfurization adsorbents in a dry state without liquid phase participation. Desulfurization agents are mostly in powder or granular form and possess adsorption and desulfurization properties. Common types of desulfurization agents include carbon materials (activated carbon / coke, activated carbon fiber, carbon nanotubes), metal oxides (activated alumina, activated manganese oxide, magnesium oxide, aluminum-based copper oxide), molecular sieves, silica gel, zeolites, solid amine organic-inorganic composite materials, and novel desulfurization agents such as metal-organic frameworks (MOFs). Calcium-based desulfurization agents are one of the commonly used desulfurization agents in dry FGD because they are simple to prepare, low in cost, and produce no secondary pollution. Compared to wet FGD, traditional dry FGD has the advantages of low cost and environmental friendliness, and its process is superior to wet FGD. Wet FGD generally suffers from wastewater generation, and subsequent flue gas treatment requires reheating. Dry FGD is relatively simple, produces less secondary pollution, the adsorbent is regenerable, the facilities are less prone to scaling and corrosion, and investment and operating costs are lower. However, traditional dry calcium-based desulfurizers have low desulfurization efficiency because the molar volume of CaSO4 generated during the desulfurization process is relatively large compared to Ca(OH)2, which blocks the pores on the particle surface and hinders the contact between the gas and the fresh desulfurizer. As a result, the non-surface part of the desulfurizer cannot be vulcanized, forming unreacted nuclei. Summary of the Invention

[0004] The purpose of this invention is to provide a calcium-based low-temperature desulfurizing agent based on pore channel formulation technology, its preparation method, and its application, in order to solve the technical problem of low desulfurization efficiency of traditional dry calcium-based desulfurizing agents.

[0005] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology, comprising the following steps: After mixing Ca(OH)2 with fly ash, binder, activator, pore-forming agent, solvent and water are added and mixed to obtain a paste mixture. After stirring the paste mixture, a clay mixture is obtained. The clay mixture is repeatedly kneaded and extruded, and then dried to obtain a desulfurizing agent.

[0006] Furthermore, the ratio of the amounts of Ca(OH)2, fly ash, binder, pore-forming agent, solvent and activator is (1900~2100)g: (220~230)g: (50~60)g: (130-140)g: (100~110)g: (100~110)g.

[0007] Furthermore, the water accounts for 25%-30% of the total mass of the desulfurizing agent; the stirring time is 1-2 hours.

[0008] Furthermore, the binder is a mixture of bentonite and polyacrylamide or a mixture of bentonite and sodium silicate; The weight ratio of polyacrylamide to bentonite is 1:10; the weight ratio of sodium silicate to bentonite is 1:10.

[0009] Furthermore, the activator is Fe2O3 or MnO2.

[0010] The solvent is NaOH; The pore-forming agent is a mixture of one of diethyl azodicarbonate, diisopropyl azodicarbonate, urea, and ammonium carbonate with zeolite; the ratio of diethyl azodicarbonate or diisopropyl azodicarbonate to zeolite is (1.6-1.8) mL: (120-130) g. The ratio of urea or ammonium carbonate to zeolite is (5-10) g: (120-130) g.

[0011] Furthermore, the drying process includes air-drying and oven-drying processes performed sequentially.

[0012] Furthermore, the air drying is performed naturally at room temperature for 12-24 hours.

[0013] Furthermore, the drying process is carried out at a temperature of 120~180℃ for a time of 150~200min.

[0014] The present invention also discloses a calcium-based low-temperature desulfurizer based on pore channel modulation technology prepared by the above preparation method.

[0015] The present invention also discloses the application of the above-mentioned calcium-based low-temperature desulfurizing agent based on pore channel mixing technology in low-temperature boiler desulfurization.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a calcium-based low-temperature desulfurizing agent based on pore configuration technology. By adding binders, activators, pore-forming agents, and solvents as raw materials to the system, and considering the strong mesoporous properties of diethyl azodicarbonate and urea, the addition of zeolite increases the number of micropores in the desulfurizing agent. The addition of diethyl azodicarbonate or urea further enhances the formation of mesopores in the desulfurizing agent, improving its internal mass transfer performance. This method can construct a three-dimensional pore structure, solving the technical problem of low desulfurization efficiency in traditional dry calcium-based desulfurizing agents.

[0017] Furthermore, the desulfurizing agent exhibits better desulfurization performance when incorporating 0.4%-1% of one of diethyl azodicarbonate, diisopropyl azodicarbonate, urea, or ammonium carbonate, and 5%-8% of zeolite. The desulfurization performance of the desulfurizing agent is not solely dependent on its specific surface area, but is more significantly influenced by the micropore area and mass transfer properties within the desulfurizing agent. In summary, the addition of zeolite increases the number of micropores in the desulfurizing agent, while the addition of other pore-forming agents induces mesoporous structures, thus improving the internal mass transfer properties of the desulfurizing agent. This allows for the construction of a three-dimensional pore structure.

[0018] The present invention also discloses a calcium-based low-temperature desulfurizer based on pore channel adjustment technology prepared by the above method. This desulfurizer improves the distribution of active sites and mass transfer performance inside the desulfurizer by incorporating a pore-forming agent to reconstruct the internal structure of the desulfurizer, thereby increasing its micropore area and improving the mass transfer channels, thus further enhancing the desulfurization performance.

[0019] Furthermore, based on the reaction mechanism of the catalyst itself, a three-dimensional pore structure was constructed, which greatly reduced the daily operating cost of the boiler while improving the utilization efficiency of the desulfurization catalyst. Attached Figure Description

[0020] Figure 1 The pore size distribution diagrams of the different desulfurizing agents obtained in Comparative Example 3 and Comparative Example 4 are shown. Wherein: a- N2 adsorption-desorption isotherms of the four desulfurizing agent samples; b- pore size distribution of the four desulfurizing agent samples; Figure 2 Desulfurization efficiency of different desulfurizing agents; Wherein: a-Ca(OH)2-DF before and after reaction with commercial calcium-based desulfurizer N2 adsorption-desorption isotherms; b-Ca(OH)2-DF before and after reaction with commercial calcium-based desulfurizer pore size distribution diagram; Figure 3 This is a morphological analysis diagram of the desulfurizing agent prepared according to the present invention; Wherein: a- SEM image of desulfurizer without iron addition (12 μm); b- SEM image of desulfurizer without iron addition (80 μm); c- SEM image of desulfurizer without iron addition (200 μm); d- SEM image of desulfurizer with iron addition (12 μm); e- SEM image of desulfurizer with iron addition (80 μm); f- SEM image of desulfurizer with iron addition (200 μm); Figure 4 This is a physical sample image of the desulfurizing agent prepared according to the present invention; Figure 5 The graph shows the change in SO2 adsorption capacity over time for Ca(OH)2-DF and commercial calcium-based desulfurizer samples. Figure 6 This presents test data on the activity of desulfurizers under different metal oxide doping conditions. Detailed Implementation

[0021] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0022] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0023] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0024] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0025] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0026] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0027] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0028] Example 1 A method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology includes the following steps: Mix 2000g Ca(OH)2 and 225g fly ash evenly, add 5g sodium silicate and 50g bentonite, then weigh 125g zeolite and 5g urea, then add 105g MnO2 as an activator, add 105g NaOH, add 950mL deionized water to obtain a paste mixture. Stir the paste mixture in a mixer for 60min to ensure that all components are mixed evenly to obtain a clay-like mixture. The obtained clay-like mixture was kneaded in a vacuum mud extruder and finally extruded into columnar desulfurizer with a diameter of 7 mm. The columnar desulfurizer was naturally air-dried at room temperature for 12 hours and then dried in an oven at 150°C for 180 minutes to obtain a calcium-based low-temperature desulfurizer based on pore configuration.

[0029] Example 2 A method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology includes the following steps: Mix 500g Ca(OH)2 and 56.25g fly ash evenly, add 1.25g sodium silicate and 12.5g bentonite, then weigh 31.25g zeolite and 0.425mL diethyl azodicarbonate, then add 26.25g Fe2O3 as an activator, add 26g NaOH, and add 237.5mL deionized water to obtain a paste-like mixture. Hydrate the paste-like mixture in a mixing mixer for 65 minutes to ensure that all components are mixed evenly to obtain a clay-like mixture. The obtained clay-like mixture was repeatedly kneaded in a screw extruder and finally extruded into a columnar desulfurizer with a diameter of 7 mm. The columnar desulfurizer was naturally air-dried at room temperature for 16 h, and then dried in an oven at 160 °C for 190 min to obtain a calcium-based low-temperature desulfurizer based on pore configuration.

[0030] Example 3 A method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology includes the following steps: Mix 4100g Ca(OH)2 with 440g fly ash evenly, add 8g polyacrylamide and 100g bentonite, then weigh 240g zeolite and 50g ammonium carbonate, then add 200g MnO2 as an activator, add 210g NaOH, add 2000mL deionized water to obtain a paste mixture. Hydrate the paste mixture in a mixing mixer for 80min to ensure that all components are mixed evenly to obtain a clay-like mixture. The obtained clay-like mixture was repeatedly kneaded in a screw extruder and finally extruded into a columnar desulfurizer with a diameter of 7 mm. The columnar desulfurizer was naturally air-dried at room temperature for 18 h, and then dried in an oven at 120 °C for 200 min to obtain a calcium-based low-temperature desulfurizer based on pore configuration.

[0031] Example 4 A method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology includes the following steps: Mix 5900g Ca(OH)2 and 680g fly ash evenly, add 15g polyacrylamide and 150g bentonite, then weigh 380g zeolite and 5mL diisopropyl azodicarbonate, then add 320g Fe2O3 as an activator, add 320g NaOH, and add 2900mL deionized water to obtain a paste-like mixture. Hydrate the paste-like mixture in a mixing mixer for 90 minutes to ensure that all components are mixed evenly to obtain a clay-like mixture. The obtained clay-like mixture was repeatedly kneaded in a screw extruder and finally extruded into a columnar desulfurizer with a diameter of 7 mm. The columnar desulfurizer was naturally air-dried at room temperature for 24 h, and then dried in an oven at 180 °C for 150 min to obtain a calcium-based low-temperature desulfurizer (Ca(OH)2-DF) based on channel formulation.

[0032] Comparative Example 1 This comparative example uses a commercial desulfurizing agent.

[0033] Comparative Example 2 Unlike Example 1, the activators used in this example were Zn2O3, CeO2, Al2O3, CuO, and Cr2O3, respectively. The remaining steps and parameters were the same as in the example, resulting in several desulfurization agent samples.

[0034] Comparative Example 3 Unlike Example 1, only azo dyes, urea, and zeolite were added as pore-forming agents, while the remaining steps and descriptions were the same as in Example 1, resulting in a desulfurizing agent sample.

[0035] Comparative Example 4 Unlike Example 1, no pore-forming agent was added, resulting in a desulfurizing agent sample.

[0036] Figure 1 The figures show the N2 adsorption and desorption isotherms and DFT model pore size distribution of the four samples obtained from Comparative Examples 3 and 4. As shown in Figure (a), all samples exhibit a typical H3-type hysteresis loop in the latter half of the relatively high pressure range (0.8~1.0), which is usually related to capillary condensation in the desulfurizer structure. Furthermore, the curves all belong to the IUPAC type IV isotherm, indicating that most desulfurizer samples exist in mesoporous form. Figure (b) shows that all samples have a wide pore size distribution, further indicating that the catalyst exists in mesoporous form and is composed of numerous irregularly stacked particles. In summary, both DEAD and urea can increase the mesopore and macropore area of ​​the samples because they have similar pore-forming principles: during drying, they decompose upon heating to produce pores, which are mostly mesopores. Zeolite, due to its high specific surface area structure, can increase the micropore area of ​​the samples through incorporation.

[0037] Figure 2 The N2 adsorption and desorption isotherms and DFT model pore size distribution diagrams for this desulfurizing agent and commercial desulfurizing agents show that although the Ca(OH)2 utilization rate of Ca(OH)2-DF is higher than that of the commercial calcium-based desulfurizing agent, the specific surface area, mesopore area, and macropore area of ​​the former are not higher than those of the latter, only the micropore area is higher. This further illustrates that desulfurization performance is not directly correlated with the specific surface area of ​​the adsorbent, but depends more on high micropore area and good mass transfer performance. The specific surface area of ​​both Ca(OH)2-DF and the commercial calcium-based desulfurizing agent decreased before and after the reaction. This is because the calcium sulfate and calcium sulfite molecules generated during the reaction adhere to the surface of the desulfurizing agent pores, causing pore blockage and reducing the number of pores. Specifically, the specific surface area of ​​the commercial desulfurizing agent decreased by 7.63%, while the decrease in the specific surface area of ​​Ca(OH)2-DF was 33.8%, much higher than that of the commercial desulfurizing agent. This indicates that during the reaction, Ca(OH)2-DF reacts with the reacting Ca... 2+ More, and its channel utilization rate is higher.

[0038] Figure 3Figure (a) shows the morphological analysis of the desulfurizing agent prepared according to this invention. As can be seen from Figure (af), the desulfurizing agents have similar morphologies, all being porous structures composed of unevenly sized nanoparticles packed together. Desulfurizing agents with such nanoparticle size often exhibit excellent desulfurization performance. Figure (a) shows that before the addition of Fe2O3, the Ca(OH)2 grains are relatively tightly packed, irregularly shaped, and angular, with indistinct surface pores and only a few large pores. Figure (b) shows that after the addition of Fe2O3, 2 μm Fe2O3 particles agglomerate on the surface of Ca(OH)2 under the action of van der Waals forces. The particles are slightly ellipsoidal, forming a rough, uneven surface, and the mesopores on the surface of the desulfurizing agent significantly increase, which is beneficial for the adsorption of SO2 molecules. Figures (c) and (d) show that numerous Ca(OH)₂ crystals aggregate into 50-150 μm agglomerates, while Fe₂O₃ particles agglomerate into 30-80 μm agglomerates, adhering to the surface of the larger Ca(OH)₂ crystals, with some located near the pores. Figures (e) and (f) indicate that after the incorporation of Fe₂O₃, the volume of the desulfurizer particle agglomerates is significantly reduced, and the dispersion phenomenon is more obvious. This suggests that Fe₂O₃ is uniformly distributed on the surface of the desulfurizer and can break up the aggregation of Ca(OH)₂ crystals. This leads to the formation of more channels inside the desulfurizer, improving its internal mass transfer performance.

[0039] Figure 4 The image shows a physical sample of the desulfurizing agent prepared according to the present invention. It can be seen that the desulfurizing agent has a smooth surface and is composed of cylindrical particles, which facilitates transportation and storage. Figure 5 The curves showing the SO2 adsorption capacity of the Ca(OH)2-DF sample and the commercial desulfurizer sample prepared for this invention, along with the change in adsorption time, reveal the following: In the initial adsorption stage, the curve slope is relatively large, indicating a rapid increase in SO2 adsorption capacity. All SO2 in the mixed gas is adsorbed onto the desulfurizer, and adsorption mainly occurs within the macropores of the desulfurizer. In the middle and later stages of adsorption, the curve slope decreases, and the desulfurization efficiency begins to decline. This is because the adsorption sites on the desulfurizer surface are gradually occupied by SO2 molecules, and the adsorption reaction shifts to the micropores, increasing mass transfer resistance. In the adsorption equilibrium stage, the adsorption capacity no longer increases, and the curve tends to parallel. Calculations show that the equilibrium adsorption capacity qe for Ca(OH)2-DF is 99.68 mg / g, and for the commercial desulfurizer it is 65.63 mg / g.

[0040] Figure 6 To test the activity of desulfurizers under different metal oxide doping, other metal oxides all showed varying degrees of enhancement effect on the low-temperature performance of the desulfurizers. The enhancement effect was ranked as follows: Fe2O3 > MnO2 > Zn2O3 > CeO2 > Al2O3 > CuO > Cr2O3.

[0041] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology, characterized in that, Includes the following steps: After mixing Ca(OH)2 with fly ash, a binder, activator, pore-forming agent, solvent and water are added and mixed to obtain a paste mixture. After stirring the paste mixture, a clay mixture is obtained. The clay mixture is repeatedly kneaded and extruded, and then dried to obtain a desulfurizing agent. The binder is a mixture of bentonite and polyacrylamide or a mixture of bentonite and sodium silicate. The weight ratio of polyacrylamide to bentonite is 1:10; the weight ratio of sodium silicate to bentonite is 1:

10. The activator is Fe2O3 or MnO2; The solvent is NaOH; The pore-forming agent is a mixture of one of diethyl azodicarbonate, diisopropyl azodicarbonate, urea, and ammonium carbonate with zeolite; the ratio of diethyl azodicarbonate or diisopropyl azodicarbonate to zeolite is (1.6-1.8) mL: (120-130) g. The ratio of urea or ammonium carbonate to zeolite is (5-10) g: (120-130) g.

2. The preparation method of a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology according to claim 1, characterized in that, The ratio of the amounts of Ca(OH)2, fly ash, binder, pore-forming agent, solvent and activator is (1900~2100)g: (220~230)g: (50~60)g: (130-140)g: (100~110)g: (100~110)g.

3. The preparation method of a calcium-based low-temperature desulfurizing agent based on pore-forming technology according to claim 1, characterized in that, The water accounts for 25%-30% of the total mass of the desulfurizing agent; the stirring time is 1-2 hours.

4. The preparation method of a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology according to claim 1, characterized in that, The drying process includes air drying and oven drying performed sequentially.

5. The preparation method of a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology according to claim 4, characterized in that, The air drying process involves air drying naturally at room temperature for 12-24 hours.

6. The method for preparing a calcium-based low-temperature desulfurizing agent based on pore channel modulation technology according to claim 4, characterized in that, The drying process is carried out at a temperature of 120~180℃ for a time of 150~200min.

7. A calcium-based low-temperature desulfurizing agent based on pore-forming technology, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 6.

8. The application of the calcium-based low-temperature desulfurizing agent based on pore channel formulation technology as described in claim 7 in low-temperature boiler desulfurization.

Citation Information

Patent Citations

  • Composition for preparing desulfurizer, desulfurizer and preparation method and application thereof

    CN112999837A

  • Medium and low temperature desulfurizer and preparation method thereof

    CN114307576A